Determining Factors of Vocational Students' Entrepreneurial Intentions in Indonesia - Hamidi, Nurhasan; Zakiah, Lina Nurul (Program MM Universitas Surabaya, 2024)
Pupose: This study aims to examined: the influence of self efficacy on the entrepreneurial intention of college students and the influence of family support on the entrepreneurial intention of college student. Method: The population of the study was students who have participated in the college level entrepreneurship development program in 2022. The sample was 239 students using the Simple Random Sampling technique. Data collection techniques used questionnaires and documentation. Data analysis method used SEM-PLS (Structural Equation Modeling-Partial Least Square) with the SmartPLS program. Result: The results of the study showed that there was a positive and significant influence of self efficacy on the entrepreneurial intention of college student and there was a positive and significant influence of family support on the entrepreneurial intention of college students